Penyuluhan Dan Edukasi Obat Bersama Snake Ladder - Nurbaiti; Gulyla Hari, Dewi (Jurnal Pengabdian UntukMu NegeRI, 2023)
Community service aims to instill wise behavior in using drugs in children from an early age, and improve health, especially in everyday life such as at school and at home. The educational media used in community service is the snake ladder. The use of snakes ladders media is a medium that is easy to understand and learn in providing effective learning. The activity participants were class 2 students of SMP Muhammadiyah 1 Pekanbaru City. The service was carried out by forming small groups consisting of 10 people per group with one instructor. The group will take part in the initial stage, namely the pre test to determine the level of knowledge of students about DaGuSiBu (Can Use, Save and Discard) drugs. The results of counseling using snake ladder media showed an increase in students' knowledge regarding DaGuSiBu medicine. In conclusion, the use of media in DaGuSiBu Medicine counseling at the school children's level is very helpful, so that school children can apply their knowledge in their surroundings. Keywords: Education, Knowledge of medicine, DaGuSiBu, Snake ladder, Effective learning